Inclusion of Ethics in the Academic Community in the World of Higher Education - Imamuddin Imamuddin; Adira Rizqi Ananda (Program Pascasarjana UIN Sumatera Utara Medan, 2021)
Education is a means and also an effort to change behavior humans (students) become better. This is because in the world education, especially higher education, does not only provide teaching to students but must also include the formation of attitudes and personality, which is important in facing the nation's moral crisis Indonesia. For this reason, education has a responsibility that is not light to prepare human resources to build the country development always closely related to developments in the times and always gives rise to new problems that have never been thought about before but still need to be addressed wisely and elegantly. The inclusion of ethics and cultural values is an effort in order to help humans to instill moral or ethical values good things in everyday life so that it will form a good individual understand moral values, be dignified and have good character and have commitment to act consistently.